INFLUENCE OF MOISTURE AND TEMPERATURE ON THE THERMAL PROPERTIES OF JACK BEAN SEEDS (CANAVALIA ENSIFORMIS) - Hussein, Jelili; Oke, Moruf Olanrewaju; Oriola, Kazeem Olaniyi; Ajetunmobi, Abimbola (Food and Feed Research, 2021)
The thermal properties (specific heat capacity, thermal conductivity, and thermal diffusivity) of Jack bean seed (Canavalia ensiformis) were determined for designing the equipment necessary for thermal processes. These thermal properties were determined at 5, 10, 15, 20, and 25 % moisture contents and temperatures at 30, 40, and 50 º C using the KD2 Pro thermal analyzer. Results showed that the specific heat capacity ranged from 1.55 to 2.47 kJ/kgK, 1.26 to 1.84 kJ/kgK and 1.32 to 1.99 kJ/kgK; thermal conductivity 0.21 to 0.47 W/mK, 0.34 to 0.52 W/mK, and 0.26 to 0.60 W/mK and thermal diffusivity 0.25 to 0.41 x 10-7 m²/s, 0.32 to 0.57 x 10-7 m²/s, and 0.32 to 0.60 x 10-7 m²/s at 30, 40, and 50 °C respectively for the moisture ranges studied. The temperature and moisture content effects were not significant (p>0.05) with specific heat and thermal diffusivity but were significant (p
Keywords: Jack beans; legume; moisture contents; temperature; thermal properties; thermal analyser